2012
DOI: 10.1002/alr.21119
|View full text |Cite
|
Sign up to set email alerts
|

When sneezing indicates the cell type

Abstract: The onset of hyperreactivity (sneezing) can be considered an important "sign" in nasal symptomatology, whose sensitivity and specificity for nonallergic "cellular" rhinitis are 79% and 93%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
7
0
2
Order By: Relevance
“…has been identified as the main cause of atopic and allergy in the tropics, 4 , 11 we observed that the frequency of positive NsIgE in the RWoA group (n = 12, 48%) was similar to in the control group (n = 5, 27.8%), and most of these patients had a negative challenge. These results support the previous data of Gelardi et al, 38 who observed NsIgE in 50% of a healthy group, and suggested that the production of NsIgE may represent a form of spontaneous immune response and is not a specific finding of nasal symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…has been identified as the main cause of atopic and allergy in the tropics, 4 , 11 we observed that the frequency of positive NsIgE in the RWoA group (n = 12, 48%) was similar to in the control group (n = 5, 27.8%), and most of these patients had a negative challenge. These results support the previous data of Gelardi et al, 38 who observed NsIgE in 50% of a healthy group, and suggested that the production of NsIgE may represent a form of spontaneous immune response and is not a specific finding of nasal symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…It can be argued that the aforementioned studies on LAR suffered from a relatively low specificity. The allergen nasal provocation test implies the administration of allergens at high concentration, that can provoke a non specific response expecially in NAR where the nasal mucosa is already inflamed [22]. Also, acoustic rhinometry is now considered poorly reproducible and difficult to standardize [23].…”
Section: Discussionmentioning
confidence: 99%
“…6,7,8,9 Based on the above considerations, it seems to be clear that nasal cytology (NC) can be an eff ective and easy-to-apply diagnostic and prognostic tool in the management of rhinitis, as it allows to detect and measure the cell population at the nasal level. 10,11 Moreover, NC is helpful to discriminate diff erent nasal disorders, to evaluate the impact of diff erent stimuli on the nose, including allergens, microbes, physical and chemical agents, and pharmacological molecules, as well as to document the eff ect of treatments. The methodology is easy and well standardized, and it mainly involves sampling, staining, and interpretation.…”
Section: Introductionmentioning
confidence: 99%